Very-Short-Term Sleep Deprivation Slows Early Recovery of Lymphocytes in Septic Patients - Zhang, Yujing; Wu, Yuming; Xu, Dan; Xiao, Ping; Xie, Bing; Huang, Haiyan; Shang, You; Yuan, Shiying; Zhang, Jiancheng (Frontiers in Medicine, 2021)
Sleep plays an important role in immune function. However, the effects of very-short-term sleep deprivation on the early recovery of immune function after sepsis remain unclear. This study was conducted in the intensive care unit to investigate the effects of 2 consecutive days of sleep deprivation (SD) on lymphocyte recovery over the following few days in septic patients who were recovering from a critical illness. The patients' self-reports of sleep quality was assessed using the Richards–Campbell Sleep Questionnaire at 0 and 24 h after inclusion. The demographic, clinical, laboratory, treatment, and outcome data were collected and compared between the good sleep group and poor sleep group. We found that 2 consecutive days of SD decreased the absolute lymphocyte count (ALC) and ALC recovery at 3 days after SD. Furthermore, post-septic poor sleep decreased the plasma levels of atrial natriuretic peptide (ANP) immediately after 2 consecutive days of SD. The ANP levels at 24 h after inclusion were positively correlated with ALC recovery, the number of CD3+ T cells, or the number of CD3+ CD4+ cells in the peripheral blood on day 5 after inclusion. Our data suggested that very-short-term poor sleep quality could slow down lymphocyte recovery over the following few days in septic patients who were recovering from a critical illness. Our results underscore the significance of very-short-term SD on serious negative effects on the immune function. Therefore, it is suggested that continuous SD or several short-term SD with short intervals should be avoided in septic patients.